The possibility of combined regulation of heat supply systems as the basis of energy efficiency (Academic journal Industrial Machine Building Civil Engineering, 2022)
The analysis of existing heating systems, as well as methods for regulating heat supply systems at the place of regulation and its parameters, was carried out. In order to maximise the efficiency of heat consumption, combined regulation should be provided, which should include local regulation and individual regulation in addition to central regulation. But this requires the reconstruction of existing single-pipe heating systems. One of the main conclusions is that modernisation of in-house systems with the existing heat source is more environmentally and energy efficient, fire and explosion safe, technologically easier to implement, and much cheaper than decentralisation of heating by installing independent heating systems with gas boilers in each apartment.
Keywords: heating system; heat meter; heat supply system; regulating valves; types of regulation